Letter (copy) : Telegram - Citrine, Walter, 1887-1983
010-0158-001 WMC/KMS/549. Secretary's. 24th July, 1936. Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue d' Orsay, Paris, vIIe. Dear Mr. Schevenels, TELEGRAM Just a note to confirm my telegram of this afternoon stating: "Favour joint meeting L.S.I. next week. Defer consideration world committee." Yours sincerely, General Secretary. 292/946/10/171